Scenario Planning for the Development of Maritime Eco-tourism Object - Zulfitri, Said Muhammad; Muluk, M. R. Khairul; Hermawan, Hermawan (UI Scholars Hub, 2016)
The regional income of the Berau Regency has been depending on the mining sector for last five years. Unfortunately, both the value and quality of the mining sector are continuously declining. These conditions threaten the economic sustainability of the Berau Regency. The eco-tourism sector, if developed by proper management especially in terms planning, may be the best way to accommodate those threats. Scenario Planning is one of suitable planning approaches that are much more capable to accommodate the complexity and the uncertainty in comparison to the conventional approach. Scenario Planning is seldom used in Indonesia, especially in tourism planning. Scenario Planning in this research paper is using the TAID method that includes tracking, analyzing, imaging and deciding. Data were collected by interviews, secondary data and observation in order to fulfill tracking step. The output of tracking step will be analyzed by cross-impact analysis in order to build scenarios in analyzing step. The output of analyzing step is used to make a vision and formulate the strategies. This paper offers four alternatives of strategies, which are Dissemination, Optimization, Strengthening and Reform. This paper also provides descriptions of the conditions of the Derawan Islands District in the next 10 years through the lenses of different perspectives of planning approach. This can be used as one of the considerations for the government to develop eco-tourism in the Derawan Islands District.